Identifikasi Jamur Penyebab Penyakit Kudis pada Buah Jeruk Siam Kintamani (Citrus nobilis L.) dan Pengendaliannya Secara Hayati - SEMBIRING, ATPENIA BR; SUDANA, I MADE; SUNITI, NI WAYAN (Jurnal Agroekoteknologi Tropika (Journal of Tropical Agroecotechnology); Vol.10, No.1, Januari 2021, 2021)
Identification of Fungi Causing Scabies Disease on Kintamani Siam Orange Fruit ( Citrus nobilis  L.) and Biological Control Siam orange is one of the leading fruit commodities in the Province of Bali, Kintamani District is one of the areas that produce siam orange in Bali. Orange fruits in Kintamani District show many symptoms of attacks on the skin of orange fruits such as scabies. Symptoms of the attack include brownish to gray spots, slightly protruding like a cork, forming a pattern on the skin of the fruit like a splash of water and rough to the touch like scabies, the cause of this disease is unknown. Orange scab disease get less attention by farmers because it is considered to have no effect on the quantity or taste of orange fruits, but orange scab disease has seriously damaged the appearance of orange fruits. The purpose of this study was to determine the pathogens that causing scurvy in orange fruits and to determine which fungi are antagonistic and able to suppress the growth of pathogens that cause scurvy in Kintamani District. The results of the isolation and molecular identification of the scurvy pathogenic fungi showed that the fungi was  Diaporthe phaseolorum  and the antagonistic fungi that could control the pathogenic fungi in vitro were  Aspergillus niger  isolated from healthy citrus fruits in the same location and the  Trichoderm a fungi group, namely  T. asperellum ,  T. harzianum ,  T. koningii ,  T. viride .